Long-Term Care Managers’ Approaches to Quality Improvement Work in Service Planning and Provision: A Qualitative Interview Study - Randi Olsson Haave; Marianne Sundlisæter Skinner; Line Melby (Global Qualitative Nursing Research)
Long-term care managers are essential in creating high-quality services. Previous research has a limited focus on managers’ practices and approaches to quality improvement work. This study aims to explore how Norwegian long-term care managers approach systematic and ad hoc quality improvement work in the context of service planning and provision. In-depth interviews were conducted with twelve long-term care managers from three municipalities and analysed using inductive thematic analysis. Three themes were identified: delegating responsibility to ensure care quality , the creation of comparable services is a goal and using quality indicators in quality improvement work . The results indicate that using key nurses’ expertise and resources were crucial approaches in the long-term care managers’ quality improvement work. Quality indicators, delegation of responsibility to other care staff and collaboration within and across municipalities were used to varying degrees. Increased collaboration with other managers, involvement of care staff and awareness and use of quality indicators are approaches that may strengthen long-term care managers’ quality improvement work.